INVESTIGATING THE IRAN PRESIDENTIAL HELICOPTER CRASH (2024): CAUSES, GEOPOLITICAL DYNAMICS, AND POLICY IMPACTS - Ruben Cornelius Siagian; Michael Haratua Rajagukguk (Arabic Literature Department, 2024)
This study investigates the helicopter crash that killed the Iranian President and seven others during a dam inauguration near the Azerbaijan border on May 9, 2024. The research examines factors contributing to the accident, including technical failures, weather conditions, human error, and potential external involvement, within the frameworks of aviation safety theory, geopolitical analysis, and crisis management. Using a multidisciplinary approach and secondary data analysis, the study identifies causal factors, evaluates their implications for aviation policies, and explores the political dynamics arising from the incident. Findings indicate that severe weather conditions, challenging topography, and possible operational errors contributed significantly to the crash. Additionally, speculation about external interference highlights the geopolitical tensions surrounding the event. The incident underscores the need for enhanced aviation safety measures and effective crisis management strategies, particularly in politically sensitive regions like the Middle East.